Comparative study of different polysaccharide‐based edible coatings on physicochemical attributes and bioactive compounds of mango cv. Dashehari fruits. Issue 1 (14th December 2022) - Gupta, Vaishali; Meena, Nirmal Kumar; Sharma, Yogendra Kumar; Choudhary, Kalpana
Abstract: Coating is an effective method in order preserve food value and prolong the shelf life of fresh fruits and vegetables. In the present investigation, the effect of various polysaccharide‐based edible coatings on fruit physicochemical and bioactive compounds of stored Dashehari mango was studied. After coating treatment with carboxymethyl cellulose (CMC) (1%), guar gum (GG) (2%) and gum acacia (GA) (2%) with control fruits were stored, and quality traits such as peel thickness, physiological loss in weight (PLW), decay, total soluble solids (TSS), sugars, titratable acidity (TA), ascorbic acid (AA), total carotenoids (TC), total chlorophyll content (TCC), total phenolic content (TPC), antioxidant capacity (AOX), and sensory traits were analyzed. According to the results, fruits treated with CMC (1%) showed higher peel thickness (0.67 mm), least PLW (10.44%), and decay (2.26%) compared to control fruits. Furthermore, at the end of storage, CMC (1%) coated fruits significantly retained the higher TA, AA, and chlorophyll content (4.30 mg 100 −1 ), 1.7‐fold higher TPC, and 2.08‐fold higher AOX capacity compared to control. Sensory results also showed higher scores and better acceptability of CMC‐coated fruits after storage of 9 days at ambient conditions. Abstract : CMC (1%) coating preserved bioactive compounds, retained the quality, and sensorial properties.